2021
DOI: 10.21203/rs.3.rs-339857/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Focal Unspecific Bone Uptake on [18F]-psma-1007 Pet: A Multicenter Retrospective Evaluation of the Distribution, Frequency, and Quantitative Parameters of a Potential Pitfall in Prostate Cancer Imaging

Abstract: PurposeImproved logistics and availability led to a rapid increase in the use of [18F]-PSMA-1007 for prostate cancer PET imaging. Initial data suggests increased uptake in benign lesions compared to [68Ga]-PSMA-11, and clinical observations found increased unspecific bone uptake (UBU). We therefore investigate the frequency and characteristics of UBU in [18F]-PSMA-1007 PET.MethodsWe retrospectively analyzed [18F]-PSMA-1007 PET scans from four centers for the presence of UBU, defined as a focal mild-to-moderate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…These additional lesions potentially upstaged the M stage categorization in 2 patients and did not impact the overall M stage categorization in rest 3 patients. Different studies 28,30–32 have reported equivocal radiotracer uptake with PSMA PET tracers at marrow and skeletal sites with a higher frequency on 18 F-PSMA-1007 than 68 Ga-PSMA-11 PET. These findings suggest that interpretation of 18 F-PSMA PET-positive skeletal lesions requires reader familiarity with known pitfalls and reporting based on the overall clinical context.…”
Section: Discussionmentioning
confidence: 97%
“…These additional lesions potentially upstaged the M stage categorization in 2 patients and did not impact the overall M stage categorization in rest 3 patients. Different studies 28,30–32 have reported equivocal radiotracer uptake with PSMA PET tracers at marrow and skeletal sites with a higher frequency on 18 F-PSMA-1007 than 68 Ga-PSMA-11 PET. These findings suggest that interpretation of 18 F-PSMA PET-positive skeletal lesions requires reader familiarity with known pitfalls and reporting based on the overall clinical context.…”
Section: Discussionmentioning
confidence: 97%
“…The compound showed a high detection rate at low PSA values and high sensitivity and specificity in both biochemical recurrence and primary staging (8,9). In some patients, nonspecific bone uptake may be a confounding factor (10).…”
Section: Introductionmentioning
confidence: 99%
“…The first tracer with broad application was [ 68 Ga]PSMA-11; with a high urinary excretion, this tracer sometimes limited the detection of local recurrence. The now also available tracer [ 18 F]PSMA-1007 is excreted more over the hepatobiliary path and reduces spill over in the pelvis; on the other hand, a higher number of unclear bone uptake are still considered limiting the specificity for bone lesions [12]. For the detection of primary tumors, however, there are no published reports about differences between both tracers.…”
Section: Introductionmentioning
confidence: 99%